2016
DOI: 10.1038/nm.4031
|View full text |Cite
|
Sign up to set email alerts
|

Human 'brite/beige' adipocytes develop from capillary networks, and their implantation improves metabolic homeostasis in mice

Abstract: The uncoupling protein 1 (UCP1) is highly expressed in brown adipose tissue, where it generates heat by uncoupling electron transport from ATP production. UCP1 is also found outside classical brown adipose tissue depots1–4, in adipocytes termed ‘brite’ (brown-in-white) or ‘beige’. In humans, the presence of ‘brite/beige’ adipocytes correlates with a lean, metabolically healthy phenotype5–8, but whether a causal relationship exists is not clear. Here we report that human ‘brite/beige’ adipocyte progenitors prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
226
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(266 citation statements)
references
References 41 publications
10
226
0
2
Order By: Relevance
“…Recent studies have also shown that BAT transplantation corrects metabolic phenotypes, and improves type 1 diabetes in streptozotocin-treated mice as well as HFD-induced insulin resistance in mice (Gunawardana & Piston 2012, Stanford et al 2013. Consistently, implantation of human beige adipocytes improves systemic glucose tolerance in HFD-induced glucose-intolerant mice (Min et al 2016). Given that preadipocytes or stem cells are also able to be differentiated into mature brown or beige adipocytes, brown or beige adipocytes transplantation may offer a practicable means for the treatment of obesity and diabetes (Bayindir et al 2015).…”
Section: :3mentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies have also shown that BAT transplantation corrects metabolic phenotypes, and improves type 1 diabetes in streptozotocin-treated mice as well as HFD-induced insulin resistance in mice (Gunawardana & Piston 2012, Stanford et al 2013. Consistently, implantation of human beige adipocytes improves systemic glucose tolerance in HFD-induced glucose-intolerant mice (Min et al 2016). Given that preadipocytes or stem cells are also able to be differentiated into mature brown or beige adipocytes, brown or beige adipocytes transplantation may offer a practicable means for the treatment of obesity and diabetes (Bayindir et al 2015).…”
Section: :3mentioning
confidence: 97%
“…In line with this, ablation of UCP1 results in disruption of diet-induced thermogenesis and exacerbation of diet-induced obesity in mice exempt from thermal stress by living at thermoneutrality (Feldmann et al 2009). Furthermore, the implantation of human beige adipocyte acquired from beige progenitors into high-fat diet (HFD)-fed mice improves systemic glucose tolerance (Min et al 2016).…”
Section: Thermogenic Function Of Brown and Beige Adipose Tissuementioning
confidence: 99%
“…Although the molecular characteristics and beiging potential of eWAsc were adequately explored, more detail is required in exploring the regulation mechanism. Similar therapies have been performed in mice by using induced mature human brown/beige adipocytes [30,42]. Although we have demonstrated that eWAsc has excellent browning potential and functionality, these human embryo-derived stem cells or adipocytes are still difficult to apply in clinical practice due to ethical and technical limitations.…”
Section: Discussionmentioning
confidence: 87%
“…Therapeutic methods targeting brown adipocytes/beige adipocytes are providing new avenues in therapies for obesity and related diseases. Although the characteristics of human adipocytes have been studied [14,17,30,31], the research related to human brown or beige adipocytes is not comprehensive, especially in terms of their characteristics, sources, development, functions, and applications. Importantly, compared to brown adipocytes, the ability to generate and isolate beige adipocytes from white adipose tissue is a growing field of research.…”
Section: Discussionmentioning
confidence: 99%
“…Maintenance of a capillary network is critically important for its metabolic function as well as survival of engrafted tissue. There is increasing evidence that angiogenic factors modu late the brown/beige differentiation and its survival after transplantation [31,32]. On the other hand, the microenvironment of the 3D culture conditions, such as stiffness or porosity of the matrix, have shown to affect the behavior of the white adipocytes [3335].…”
Section: Introductionmentioning
confidence: 99%